Interactive Cover Design Considering Physical Constraints - Igarashi, Yuki; Igarashi, Takeo; Suzuki, Hiromasa (Computer graphics forum, 2009)
We developed an interactive system to design a customized cover for a given three‐dimensional (3D) object such as a camera, teapot, or car. The system first computes the convex hull of the input geometry. The user segments it into several cloth patches by drawing on the 3D surface. This paper provides two technical contributions. First, it introduces a specialized flattening algorithm for cover patches. It makes each two‐dimensional edge in the flattened pattern equal to or longer than the original 3D edge; a smaller patch would fail to cover the object, and a larger patch would result in extra wrinkles. Second, it introduces a mechanism to verify that the user‐specified opening would be large enough for the object to be removed. Starting with the initial configuration, the system virtually “pulls” the object out of the cover while avoiding excessive stretching of cloth patches. We used the system to design real covers and confirmed that it functions as intended.